Risk factors and prevalence of newborn hearing loss in a private health care system of Porto Velho, Northern Brazil - Juliana Santos de Oliveira; Liliane Barbosa Rodrigues; Fernanda Soares Aurélio; Virgínia Braz da Silva (Sociedade de Pediatria de São Paulo, 2013)
OBJECTIVE: To determine the prevalence of hearing loss and to analyze the results of newborn hearing screening and audiological diagnosis in private health care systems. METHODS Cross-sectional and retrospective study in a database of newborn hearing screening performed by a private clinic in neonates born in private hospitals of Porto Velho, Rondônia, Northern Brazil. The screening results, the risk for hearing loss, the risk indicators for hearing loss and the diagnosis were descriptively analyzed. Newborns cared in rooming in with their mothers were compared to those admitted to the Intensive Care Unit regarding risk factors for hearing loss. RESULTS: Among 1,146 (100%) enrolled newborns, 1,064 (92.8%) passed and 82 (7.2%) failed the hearing screening. Among all screened neonates, 1,063 (92.8%) were cared in rooming and 83 (7.2%) needed intensive care; 986 (86.0%) were considered at low risk and 160 (14.0%) at high risk for hearing problems. Of the 160 patients identified as having high risk for hearing loss, 83 (37.7%) were admitted to an hospitalized in the Intensive Care Unit, 76 (34.5%) used ototoxic drugs and 38 (17.2%) had a family history of hearing loss in childhood. Hearing loss was diagnosed in two patients (0.2% of the screened sample). CONCLUSIONS: The prevalence of hearing loss in newborns from private hospitals was two cases per 1,000 evaluated patients. The use of ototoxic drugs, admission to Intensive Care Unit and family history of hearing loss were the most common risk factors for hearing loss in the studied population.